Implementation of the Problem-Based Learning Model to Build Adiwiyata Schools through Strengthening Environmental Care Character in Elementary Schools - Sri Sunarni; Wakhudin Wakhudin (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in building Adiwiyata Schools through the strengthening of environmental care character in elementary schools. Using a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation. The results of the study show that the application of PBL successfully increased student engagement in various environmental activities such as waste management, reforestation, and water conservation, while also developing environmental care character traits including responsibility, awareness, and cooperation. Support from teachers, principals, parents, and the school environment proved to be crucial factors in the successful implementation of PBL, although several challenges such as limited facilities and student motivation still need to be addressed. The study concludes that PBL is an effective learning strategy to support the Adiwiyata School program and to foster environmental care character from an early age.